3D-QSAR and Molecular Docking Studies on Benzimidazole Derivatives: Validation of Experimental Inhibitory Potencies Towards COX-1 (PDB: 2OYE) and COX-2 (PDB: 4COX) - Kute, Pruthviraj Vijay; Bhor, Rohit Jaysing; Kolhe, Mahesh Hari; Bhosale, Harshada Shubhash; Tambe, Pornima Ramdas; Bhoknal, Mayuri Rajesh; Jadhav, Pratibha Shankar; Avhad, Swapnali Baban; Dharam, Mayuri Girish; Mule, Ajay Sanjay (International Journal of Pharmaceutical Investigation, 2026)
Background The computational study of benzimidazole derivatives is the main topic of this article. All compounds' cytotoxicity against inflammation was assessed, and the outcomes showed that several of them had strong inhibitions. This study investigates the many pharmacological characteristics of benzimidazole derivatives, including their anticancer, antibacterial, antioxidant, anti-inflammatory, and anticonvulsant effects. The proposed approach summarizes each activity in silico research. The structure-activity correlations and pharmacological effects of compounds containing benzimidazole are examined in this study. Using a variety of computational techniques, in silico studies allow for forecasting structural changes and how they would impact the pharmacological properties as well as the efficiency of these modifications. Materials and Methods Molecular Design Suite was used to conduct Combi Lab investigations and 3D-QSAR. Schrodinger Maestro was used for the molecular docking investigation. Results Seven compounds (PVK1 and PVK15) in a library of 15 compounds created using a combinatorial approach demonstrated superior projected biological activity than the dataset's most active molecule. These chemicals exhibited proximal contact with amino acid residues on COX-2 such as TYR355 and/or ARG120. Conclusion This study determined the structural elements affecting by carefully changing the substituents, ring modifications, and linker groups. The logical creation and optimization of more powerful and selective molecules is made possible by these discoveries. In contrast to the reference ligand, the current study produced more powerful benzimidazoles as inhibiting compounds for COX-2 with excellent interaction. The study's findings could aid in the creation of new COX-2 inhibitors to treat inflammatory conditions.
Keywords: ADMET; Benzimidazole; COX 1; COX 2; Inflammation; Molecular Docking